Internet, News, and Political Trust: The Difference between Social Media and Online Media Outlets. Issue 5 (5th June 2015) - Ceron, Andrea
Abstract: What is the relationship between Internet usage and political trust? To answer this question, we performed a cross-sectional analysis of Eurobarometer survey data related to 27 countries and a supervised sentiment analysis of online political information broadcast during the Italian debate on the reform of public funding of parties. The results disclose the differences between Web 1.0 websites and Web 2.0 social media, showing that consumption of news from information/news websites is positively associated with higher trust, while access to information available on social media is linked with lower trust. This has implications for the debate on social media as a public sphere and for the tension between professional and citizen journalism.